Optoelectronic photoinduced charge transfer system with mu 3PhN-Ru-3 cluster functionalized single-walled carbon nanotubes - Lee, Wonjoo; Koo, Gumae; Ogale, Satishchandra B.; Han, Sung-Hwan (Journal of Materials Chemistry C, 2009)
Optoelectronic photoinduced charges have been attracting great attention lately in view of their applicability to diverse optoelectronic device systems. Here, we report the design and implementation of a charge transfer system based on triruthenium (Ru) cluster compounds on viologen modified single-walled carbon nanotubes (V-SWNTs) by an in situ preparation method. We examine the photoinduced (intensity dependent and temporal) changes in the transport properties of the Ru-cluster functionalized V-SWNT coating and identify the possible charge transfer mechanism. Furthermore, we demonstrate the applicability of such Ru-cluster functionalized V-SWNT films to photoelectrochemical cells.

Off-stoichiometric nickel cobaltite nanoparticles: thermal stability, magnetization, and neutron diffraction studies - Verma, Seema; Kumar, Amit; Pravarthana, D.; Deshpande, Aparna; Ogale, Satishchandra B.; Yusuf, S. M. (Journal of Physical Chemistry C, 2014)
In the present investigation, we report a detailed examination of the effect of off-stoichiometry introduced in NiCo2O4 by adding excess cobalt. Thus, we compare and analyze the structural and magnetic properties of the Ni075Co2.25O4 and NiCo2O4 cubic systems. A low temperature combustion method was utilized to synthesize stoichiometric (NiCo2O4) and off-stoichiometric (Ni0.75Co2.25O4) nanoparticles on a large scale. The X-ray diffraction pattern for the sample annealed at high temperature (773 K) shows the presence of a much less intense NiO phase (similar to 2-5%) in Ni0.75Co2.25O4 as compared to that in the case of NiCo2O4 sample (similar to 15-20%). The Ni 2p and Co 2p XPS spectra reveal the coexistence of Ni2+, Ni3+, Co2+, and Co3+ species on the surface of both the NiCo2O4 and Ni0.75Co2.23O4 samples in differing proportions. In addition to the basic magnetic characterizations using PPMS, these were also analyzed by neutron diffraction. The off-stoichiometric Ni0.75Co2.25O4 sample shows an interesting magnetic phase conversion from frustrated dipolar system to an enhanced magnetic ordering upon annealing. Local moments on the lattice sites of NiCo2O4 and Ni0.75Co2.25O4 samples are further compared by neutron diffraction confirming stronger ordered moments and enhanced structural and thermal stability for the Ni0.75Co2.25O4 sample.

On-axis pulsed laser deposition of hybrid perovskite films for solar cell and broadband photo-sensor applications - Bansode, Umesh; Ogale, Satishchandra B. (Journal of Applied Physics, 2017)
High quality hybrid perovskite films are grown by the pulsed laser deposition (PLD) process through target stoichiometry and gas ambient control in the commonly used on-axis geometry which is compatible with PLD of other materials such as metal oxides. The use of an off-stoichiometric target and a momentum softening gas mixture of argon and hydrogen (90%:10%) is shown to yield dense films in the on-axis geometry with excellent stoichiometry and optical quality. The band gap can be easily tuned from 1.6 to 2.3 eV with either mixed halide composite target or successive depositions of inter-diffusing MAPbBr(3) and MAPbI(3) layers. A photosensor based on PLD grown MAPbI(3) is shown to render impressive performance over the broad range of wavelengths from 375 to 800 nm at a voltage of 5V bias. A planar heterojunction solar cell based on the dry-processed on-axis PLD grown film exhibits a champion conversion efficiency of 10.9%. A heterostructure comprising in situ pulsed laser deposited Cu2O (p-type) followed by the hybrid perovskite film shows a rectifying characteristic and photoresponse.